"Getting it right when it goes wrong – Effective bereavement care requires training of the whole maternity team". (April 2022) - Aggarwal, Neelam; Moatti, Zoe
Abstract: Stillbirth or neonatal death is one of the most traumatic and distressing life experiences with negative psychosocial effects. Perinatal grief is natural and understandable, and, if not recognized and well supported, may lead to long-term harmful effects. Harm may also be caused to the other surviving siblings, families, and next generation. This can be helped by effective bereavement care. Bereavement care is an area of enormous needs, relatively untraveled road. Though the loss cannot be undone, but a negative impact can be minimized by compassionate supportive care. This chapter will focus on the need of a trained team for effective bereavement care. Principles of evidence-based best practices from the literature will be reviewed and translated into key practice implications. An emphasis is laid on a structured training involving the whole team. We hope this will help in day-to-day situation handling so as to prevent the harm associated with unaddressed grief. Areas of gap with the further need of research are highlighted. Highlights: Stillbirth is one of the most traumatic life experiences associated with long-lasting negative psychosocial impacts. Empathic and compassionate care positively influences the parents' recovery. Evidence demonstrates considerable variation in care and unmet parental needs. Providers are not usually trained to deal with the grief of bereaved parents and their own needs. Training is needed for the whole team to be able to exhibit appropriate behaviors to prevent further harm.